Diffuse Lewy body disease manifesting as corticobasal syndrome: A rare form of Lewy body disease. (17th July 2018) - Kasanuki, Koji; Josephs, Keith A.; Ferman, Tanis J.; Murray, Melissa E.; Koga, Shunsuke; Konno, Takuya; Sakae, Nobutaka; Parks, Adam; Uitti, Ryan J.; Van Gerpen, Jay A.; Graff-Radford, Neill R.; Wszolek, Zbigniew K.; et al.
Abstract : Objective: To describe clinical and pathologic characteristics of diffuse Lewy body disease (DLBD) manifesting as corticobasal syndrome (CBS). Methods: In 523 autopsy-confirmed cases of DLBD, we identified 11 patients diagnosed with CBS. For comparison, we studied 22 DLBD brains with antemortem presentation of dementia with Lewy bodies (DLB). Given previous studies suggesting the importance of pathology in peri-Rolandic cortices in CBS, we used digital pathology to count Lewy bodies and to quantify intracytoplasmic and neuritic α-synuclein and phospho-tau burden in the motor cortex. Results: DLBD patients with antemortem features of CBS were significantly younger at disease onset and less likely to have REM sleep behavior disorder than DLBD cases who met clinical criteria for DLB during life. Patients with DLBD manifesting as CBS had more Lewy bodies in the motor cortex than DLBD manifesting as clinically probable DLB. Three cases had concomitant progressive supranuclear palsy and 4 cases had concomitant Alzheimer disease as probable correlates of CBS. Conclusion: The neuropathology underlying CBS is heterogeneous, including corticobasal degeneration, Alzheimer disease, and progressive supranuclear palsy. This study suggests that atypical variants of Lewy body disease with severe peri-Rolandic Lewy-related pathology can present clinically as CBS. Patients with DLBD who present as CBS tend to have an earlier age at onset and are less likely to have clinical features of DLB, such as dream enactment behavior during sleep, visual hallucinations, and levodopa-responsive parkinsonism. Future studies with biofluid or molecular imaging biomarkers for α-synuclein will permit better recognition of this uncommon pathologic substrate of CBS.